2015
DOI: 10.4067/s0717-66432015000100011
|View full text |Cite
|
Sign up to set email alerts
|

Conductancia hidráulica foliar y vulnerabilidad a la cavitación disminuyen con la altitud en Phacelia secunda J.F. Gmel. (Boraginaceae)

Abstract: High mountain ecosystems are characterized by freezing temperatures. Freeze-thaw events can induce embolism in plant xylem. The risk of embolism increases with the conduit diameter, because wider xylem vessels can contain larger amounts of dissolved gas that after water freeze may form big bubbles producing cavitation. Thus smaller vessels could be advantageous in habitats prone to freezing events. However, smaller conduits decrease hydraulic conductance. The leaf hydraulic conductance (Kf) is a measure of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…The reduction of hydraulic efficiency may be related to the limitation in d, d h and D a (Table S1). Mean tracheid diameter decreased while VD increased with increasing elevation, which is consistent with previous studies (Hernandez-Fuentes et al, 2015) and supports the hypothesis that trees growing in high elevations subjected to frost drought have smaller tracheid diameters than the same species in warmer areas at lower elevations (Cabral et al, 2016). When temperatures drop in October and frost drought can occur at higher elevations in winter (Charrier et al, 2017;Earles et al, 2018), embolism formation can be induced.…”
Section: Influence Of Environmental Conditions On Xylem Water Transpo...supporting
confidence: 91%
See 1 more Smart Citation
“…The reduction of hydraulic efficiency may be related to the limitation in d, d h and D a (Table S1). Mean tracheid diameter decreased while VD increased with increasing elevation, which is consistent with previous studies (Hernandez-Fuentes et al, 2015) and supports the hypothesis that trees growing in high elevations subjected to frost drought have smaller tracheid diameters than the same species in warmer areas at lower elevations (Cabral et al, 2016). When temperatures drop in October and frost drought can occur at higher elevations in winter (Charrier et al, 2017;Earles et al, 2018), embolism formation can be induced.…”
Section: Influence Of Environmental Conditions On Xylem Water Transpo...supporting
confidence: 91%
“…Subalpine ecosystems are characterized by significant elevational differences in environmental factors, among which temperature is most relevant for plants (Hernandez‐Fuentes et al, 2015). The decrease in temperature with elevation will increase the viscosity of water (about 2.4% per kelvin; Tyree & Zimmermann, 2002) and reduce the water transport efficiency (Arias et al, 2021; Sellin & Kupper, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…En contraste, a mayor elevación no hubo diferencias en los potenciales hídricos del suelo entre OTCs y espacios abiertos, con valores cercanos a -0.3 MPa (Sanfuentes et al 2012). Resultados similares, en relación con el efecto del calentamiento sobre la ganancia de carbono en Phacelia secunda a diferentes altitudes, fueron reportados por Hernández-Fuentes et al (2015), donde nuevamente evidenciaron disminución de la tasa de fotosíntesis con calentamiento a 1600 y 2800 m de altitud, pero efectos positivos a 3600 m. Estos resultados nuevamente apuntan a consecuencias diferenciales del calentamiento sobre el desempeño de una misma especies diferentes elevaciones: mientras en altitudes mayores el calentamiento afecta positivamente la ganancia de carbono, en altitudes menores la disminuye. Ambos estudios apuntan a que esta respuesta diferencial podría estar dada por la interacción entre el calentamiento y la disponibilidad de agua en el suelo.…”
Section: Consecuencias Del Calentamiento Sobre El Desempeño Fotosintéticounclassified
“…Several studies have shown that populations of this species growing at different elevations show morphological, anatomical, and physiological variations related to the contrasting environmental conditions found at different elevations (Cavieres 2000; Hernandez‐Fuentes et al . 2015; Hernández‐Fuentes et al . 2015, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(Boraginaceae) is a perennial herb with a wide altitudinal distribution in the Andes of central Chile. Several studies have shown that populations of this species growing at different elevations show morphological, anatomical, and physiological variations related to the contrasting environmental conditions found at different elevations (Cavieres 2000;Hernandez-Fuentes et al 2015;Hernández-Fuentes et al 2015. For instance, Cavieres (2000) showed that rosettes of plants from low elevations (1600 m) are smaller in diameter but taller than plants from high elevations (e.g., 3600 m).…”
Section: Introductionmentioning
confidence: 99%